ISLAMISASI DI RIAU (Kajian Sejarah dan Budaya Tentang Masuk dan Berkembangnya Islam di Kuntu Kampar) - Elya Roza (Sosial Budaya, 2015)
This paper is about a historical research aimed to understand the islamization process in Kuntu, Kampar Regency, Riau Province. Historicaly, an Islmaic preacher from middle east named Syekh Burhanudin was a missionary that introduced Islamic teaching in Kuntu. This teaching did not only played a big role in the life of people in Kuntu but it also influenced others region in Riau Province in every walks of life. The wide spread of Islamic teaching boiled down to the humble personality of Syekh Burhanudin on promoting Islamic values as what others Islam missionaries did across Indonesia. At the end, Islamic values play an important role on cultre and character of people in Kuntu and Indonesia.